Implementation of mental health policies and relevance of the management of violence against women in Peru´s healthcare system - Herrera-Lopez, Vanessa E. (2025)
This article presents an analysis of the impact of violence on the mental health of its women victims in Peru, covering as well critical periods such as those triggered by the COVID-19 pandemic. The Violence Against Women (VAW) and the implementation of mental healthcare policies in Peru are critically examined, highlighting both progress made and the remaining challenges. The need to strengthen the competencies of healthcare teams through operational training models designed to enhance the response to VAW at the primary care level is duly examined. Significant obstacles, such as insufficient resources, lack of ongoing training for healthcare professionals, and cultural barriers that hinder effective interventions, are identified. A comprehensive approach aimed not only at reinforcing mental health services but also improving the coordination between key sectors and institutions, is proposed. Furthermore, the urgency of developing educational and awareness strategies, both within the healthcare system and in the broader community to effectively prevent and address VAW, are emphasized. Finally, the article underscores the importance of a robust leadership in all public health policy areas, an essential approach to ensure that VAW is recognized and treated as a strategic priority while guaranteeing a sustainable and effective response over the long term.